Early Dyadic Communication: Microanalysis of Eight Cases - Sanabria-León, Jorge Rafael (2020)
Objective. This paper characterizes mother-baby interaction styles for the purpose of identifying dyadic bonding throughout the first year of life. The Forms of Interaction are emphasized as a central concept for the incorporation of the subject into communication and then to language. Method. Records of natural interactions from eight dyads to six weeks, six months and one year of age identify the progressive constitution of the dyadic communication system. Results. The elucidation of body signs and the emergence of emotional regulation at six weeks, the interplay with social scenes at six months, and the establishment of the dyadic semantic field at one year are salient features that intertwine during the process. Triangulation with the social environment is a constant within the interaction.